How do you factor $9{{x}^{2}}-6x-15$ ?
Answer
Verified
438.9k+ views
Hint: When we factorize a quadratic equation $a{{x}^{2}}+bx+c$ we write $bx$ as $mx+nx$ where $m+n=b$ and $mn=ac$, then we can easily factorize the equation. We can split -6x to 9x and -15x to solve this question.
Complete step by step solution:
The given equation is $9{{x}^{2}}-6x-15$ which is a quadratic equation. if we compare the equation to standard quadratic equation $a{{x}^{2}}+bx+c$ then a = 9, b = -6 and c = -15
To factor a quadratic equation, we can find two numbers m and n such that the sum of m and n is equal to b and the product of m and n is $ac$. Then we can split $bx$ to $mx+nx$ then we can factor the equation easily.
In our case ac = -135 and b = -6
So pair of 2 numbers whose product is -135 and sum -6 is ( 9 ,-15)
We can -6x split to 9x – 15x
So $9{{x}^{2}}-6x-15=9{{x}^{2}}+9x-15x-15$
Taking 9x common in the first half of the equation and taking -15x common in the second half of the equation.
$\Rightarrow 9{{x}^{2}}-6x-15=9x\left( x+1 \right)-15\left( x+1 \right)$
Taking x + 1 common
$\Rightarrow 9{{x}^{2}}-6x-15=\left( 9x-15 \right)\left( x+1 \right)$
We can take 3 common from 9x – 15
$\Rightarrow 9{{x}^{2}}-6x-15=3\left( 3x-5 \right)\left( x+1 \right)$
Note:
While factoring a quadratic equation we can’t always split $bx$ such that their product is equal to ac because sometimes the roots can be irrational numbers. So in that case we can try the complete square method to factorize the equation.
Complete step by step solution:
The given equation is $9{{x}^{2}}-6x-15$ which is a quadratic equation. if we compare the equation to standard quadratic equation $a{{x}^{2}}+bx+c$ then a = 9, b = -6 and c = -15
To factor a quadratic equation, we can find two numbers m and n such that the sum of m and n is equal to b and the product of m and n is $ac$. Then we can split $bx$ to $mx+nx$ then we can factor the equation easily.
In our case ac = -135 and b = -6
So pair of 2 numbers whose product is -135 and sum -6 is ( 9 ,-15)
We can -6x split to 9x – 15x
So $9{{x}^{2}}-6x-15=9{{x}^{2}}+9x-15x-15$
Taking 9x common in the first half of the equation and taking -15x common in the second half of the equation.
$\Rightarrow 9{{x}^{2}}-6x-15=9x\left( x+1 \right)-15\left( x+1 \right)$
Taking x + 1 common
$\Rightarrow 9{{x}^{2}}-6x-15=\left( 9x-15 \right)\left( x+1 \right)$
We can take 3 common from 9x – 15
$\Rightarrow 9{{x}^{2}}-6x-15=3\left( 3x-5 \right)\left( x+1 \right)$
Note:
While factoring a quadratic equation we can’t always split $bx$ such that their product is equal to ac because sometimes the roots can be irrational numbers. So in that case we can try the complete square method to factorize the equation.
Recently Updated Pages
A uniform rod of length l and mass m is free to rotate class 10 physics CBSE
Solve the following pairs of linear equations by elimination class 10 maths CBSE
What could be the possible ones digits of the square class 10 maths CBSE
Where was the Great Bath found A Harappa B Mohenjodaro class 10 social science CBSE
PQ is a tangent to a circle with centre O at the point class 10 maths CBSE
The measures of two adjacent sides of a parallelogram class 10 maths CBSE
Trending doubts
Imagine that you have the opportunity to interview class 10 english CBSE
Find the area of the minor segment of a circle of radius class 10 maths CBSE
Fill the blanks with proper collective nouns 1 A of class 10 english CBSE
Frogs can live both on land and in water name the adaptations class 10 biology CBSE
Fill in the blank One of the students absent yesterday class 10 english CBSE
Write a letter to the Principal of your school requesting class 10 english CBSE